2021
DOI: 10.14740/wjon1371
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychological Distress of Lung Cancer Patients Undergoing Chemotherapy

Abstract: Background: Patients with lung cancer often experience multiple symptoms associated with both the disease itself and the treatment. The disease and therapy-related adverse effects may lead to poor quality of life (QoL) and increased psychological distress. The aim of this study was to investigate the QoL and psychological distress of patients with lung cancer. The relationship between these two aspects was also an area of focus.Methods: This was a quantitative descriptive study. Data collection was done using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
(36 reference statements)
1
10
0
2
Order By: Relevance
“…Recent studies have found a strong link between depression and anxiety in individuals with lung and prostate cancers, which further supports our findings. [ 32 33 ] More research is needed to ensure that people with lung and prostate cancers are appropriately assessed and treated for psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found a strong link between depression and anxiety in individuals with lung and prostate cancers, which further supports our findings. [ 32 33 ] More research is needed to ensure that people with lung and prostate cancers are appropriately assessed and treated for psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…13,27 As lung cancer patients experience greater psychological stress during disease treatment, they are prone to denial and self-doubt, which can increase feelings of shame. 28 Studies have shown that shame can increase cortisol. 29,30 During the intervention, participants’ shared experience of laughter reduces shame.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identi ed that the main factors associated with low mental quality of life and low physical quality of life in people with cancer were nonspeci c indicators of mental health such as having severemoderate stress and emotional distress. Several cross-sectional studies have previously identi ed an inverse relationship between quality of life stress and emotional distress in cancer patients [68][69][70].…”
Section: Mental Health and Quality Of Lifementioning
confidence: 99%